The Role of Educational and Religious Institutions in Combating Violence, Extremism, and Terrorism - Al-Halawani, Dr. Sohier Zaki Al-Halawani; Saeb, Dr. Wamedh Faris Saeb (Sulaimani Journal for Humanities, 2026)
Educational and religious institutions play a pivotal role in combating violence, extremism, and terrorism through education and awareness. These institutions promote values of tolerance and mutual respect and support the building of a cohesive society. This is achieved by raising awareness in schools and universities, highlighting the importance of dialogue and peaceful coexistence through curricula that focus on human rights and citizenship. In contrast, religious institutions work to correct the erroneous religious concepts exploited by extremists, promoting a correct understanding of Islam based on love and peace. Through these joint efforts, societies can reduce the risks of extremism and violence, and foster a safe and stable environment for future generations. This research addresses a main issue, which includes several questions: How can educational and religious institutions enhance efforts to combat violence, extremism, and terrorism in contemporary societies? · What strategies can schools and universities adopt to promote values of tolerance and mutual respect? · How can religious institutions correct the erroneous religious concepts exploited by extremists?
Keywords: educational institutions; religious institutions; violence; extremism; terrorism